Relationship of Nurse-Led Education Interventions to Liver Transplant Early Readmission. (June 2020) - Dols, Jean Dowling; Chargualaf, Katie A.; Gordon, Amy; Pomerleau, Theresa; Mendoza, Anna; Schwarzbach, Clare; Gonzalez, Marcela
Introduction: Early hospital readmission following liver transplantation is associated with lower survival and worse long-term graft function. Language, cultural practices, and health literacy influence patient understanding of posttransplant care education. Complex medication regimes, changes in metabolism and nutrition absorption, and infection/rejection further complicate the prevention of readmission. Purpose: The purpose of this study was to compare the 30-day readmissions of single-organ liver transplant recipients for 1-year prior and 1-year following the implementation of nurse-led education. The study examined the demographics, clinical characteristics, and 30-day readmissions of 35 liver transplant recipients who participated in the newly designed nurse-led education and 51 liver transplant recipients who experienced the prior post-liver transplant education. Design: A single-center, correlational study with a convenience sample was conducted at a Hispanic-serving South Texas hospital. The new education intervention maintained the standard education and added twice-daily mutual patient-focused goal setting between the nurse and the recipient that aligned with readiness for discharge activities/goals, structured education using abbreviated handouts written at a second-grade level available in both English and Spanish, and the use of repetition through multimodal methods. Results: The odds for 30-day readmissions the year prior to the nurse-led patient education intervention were 2.088 times greater than the year following the implementation. Thirty-day readmissions were reduced by 16.3% from the 2017 cohort to the 2018 cohort. Discussion: Understanding unique risk factors facilitates structured patient education which can be individualized to the patient and caregiver including collaborative nurse–patient goals.